2014
DOI: 10.3947/ic.2014.46.2.120
|View full text |Cite
|
Sign up to set email alerts
|

A Case of Ventriculitis Associated with Renal Abscess Caused by Serotype K1Klebsiella pneumoniae

Abstract: Recently, serotype K1 Klebsiella pneumoniae has been a major agent of an invasive syndrome characterized by liver abscess and its metastatic infection. Extrahepatic infection and its characteristics in patients with renal abscess caused by K. pneumoniae are poorly understood, and few cases of central nervous system infection have been reported. This is a report of 80-year-old woman with uncontrolled type 2 diabetes mellitus with renal abscess caused by serotype K1 K. pneumoniae, complicated with ventriculitis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 17 publications
0
10
0
Order By: Relevance
“…Different from “classic” K. pneumoniae (cKp), the new variants of K. pneumoniae exhibit enhanced virulence features. In addition to PLA, hvKp also cause other invasive diseases including abscesses at other sites (e.g., eyes, brain, prostate, and kidney), necrotizing fasciitis, and severe pneumonia with bacteremia (Hu et al, 1999; Saccente, 1999; Hyun et al, 2014; Kim et al, 2014). Although hvKp infection appears to occur often in diabetic patients, a particularly disconcerting problem is its ability to cause community-acquired, life-threatening infection among young and healthy individuals (Pomakova et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Different from “classic” K. pneumoniae (cKp), the new variants of K. pneumoniae exhibit enhanced virulence features. In addition to PLA, hvKp also cause other invasive diseases including abscesses at other sites (e.g., eyes, brain, prostate, and kidney), necrotizing fasciitis, and severe pneumonia with bacteremia (Hu et al, 1999; Saccente, 1999; Hyun et al, 2014; Kim et al, 2014). Although hvKp infection appears to occur often in diabetic patients, a particularly disconcerting problem is its ability to cause community-acquired, life-threatening infection among young and healthy individuals (Pomakova et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Life-threatening liver abscesses, pneumonia, meningitis, bloodstream infections (BSI) or endophthalmitis caused by hvKP have been increasingly reported in the USA, Brazil, Germany, Japan, and Australia [2][3][4][5][6]. These infections are often community-acquired [7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…Multivariate logistic regression analyses demonstrated that the K1 strain was the sole significant risk factor for metastatic complications (adjusted odds ratio, 4.8; 95% confidence interval, 1.5-15.7, p = 0.009), strongly suggesting that the K1 strains should be recognized as a distinct virulent organism. In addition, such metastatic complications have been reported in patients with K1 strains without hepatic involvement, suggesting that their development is unrelated to the presence of PLA (25,26). Thus, our case highlights the importance of considering serotype K1 hvKp as a rare causative agent of communityacquired brain abscess and of screening for the primary site of infection.…”
Section: Discussionmentioning
confidence: 54%
“…In fact, there are several reported cases of PLA with hematogenous spread to the kidney, perirenal tissues, and prostate, leading to local abscess formation (23). Conversely, several hvKp cases with community-acquired UTIs without PLA have also been reported (24)(25)(26). Similarly, the main source of infection in our case was the prostate gland, and concomitant liver abscess was highly likely secondary to the primary prostatic infection.…”
Section: Discussionmentioning
confidence: 55%